Analisis Teknik Renang Gaya Bebas Pada Mata Kuliah Renang - Ruman Ruman; Raditya Pratama; Khakim Khakim (Lembaga Pengembangan Kinerja Dosen, 2022)
The aim of this research was to determine the level of basic freestyle swimming techniques of students in the Swimming Subject of the Health and Recreation Physical Education Study Program. This research is a descriptive study which aims to describe how to analyze basic freestyle swimming movement techniques for Swimming Course students. The overall research results of the 30 students of the Swimming Subject, Physical Education, Health and Recreation Study Program, STKIP Darussalam Cilacap who were sampled, showed that the level of mastery of freestyle swimming techniques was 67%. classified as good, with an error rate of 33%.